Association of Nondiscrimination Policies With Mental Health Among Gender Minority Individuals - McDowell, Alex (JAMA Psychiatry, 2020)
IMPORTANCE: In the past decade, many states have implemented policies prohibiting private health insurers from discriminating based on gender identity. Policies banning discrimination have the potential to improve access to care and health outcomes among gender minority (ie, transgender and gender diverse) populations. OBJECTIVE: To evaluate whether state-level nondiscrimination policies are associated with suicidality and inpatient mental health hospitalizations among privately insured gender minority individuals. DESIGN, SETTING, AND PARTICIPANTS: In this cohort study, difference-in-differences analysis comparing changes in mental health outcomes among gender minority enrollees before and after states implemented nondiscrimination policies in 2009-2017 was conducted. A sample of gender minority children and adults was identified using gender minority–related diagnosis codes obtained from private health insurance claims. The present study was conducted from August 1, 2018, to September 1, 2019. EXPOSURE: Living in states that implemented policies banning discrimination based on gender identity in 2013, 2014, 2015, and 2016. MAIN OUTCOMES AND MEASURES: The primary outcome was suicidality. The secondary outcome was inpatient mental health hospitalization. RESULTS: The study population included 28 980 unique gender minority enrollees (mean [SD] age, 26.5 [15] years) from 2009 to 2017. Relative to comparison states, suicidality decreased in the first year after policy implementation in the 2014 policy cohort (odds ratio [OR], 0.72; 95% CI, 0.58-0.90; P = .005), the 2015 policy cohort (OR, 0.50; 95% CI, 0.39-0.64; P < .001), and the 2016 policy cohort (OR, 0.61; 95% CI, 0.44-0.85; P = .004). This decrease persisted to the second postimplementation year for the 2014 policy cohort (OR, 0.48; 95% CI, 0.41-0.57; P < .001) but not for the 2015 policy cohort (OR, 0.81; 95% CI, 0.47-1.38; P = .43). The 2013 policy cohort experienced no significant change in suicidality after policy implementation in all 4 postimplementation years (2014: OR, 1.19; 95% CI, 0.85-1.67; P = .31; 2015: OR, 0.94; 95% CI, 0.73-1.20; P = .61; 2016: OR, 0.82; 95% CI, 0.65-1.03; P = .10; and 2017: OR, 1.29; 95% CI, 0.90-1.88; P = .18). Mental health hospitalization rates generally decreased or stayed the same for individuals living in policy states vs the comparison group. CONCLUSIONS AND RELEVANCE: Implementation of a state-level nondiscrimination policy appears to be associated with decreased or no changes in suicidality among gender minority individuals living in states that implemented these policies from 2013 to 2016. Given high rates of suicidality among gender minority individuals in the US, health insurance nondiscrimination policies may offer a mechanism for reducing barriers to care and mitigating discrimination.